Mean Reversion of the German City System After the WWII Bombing of Cities: What Is the Mean? - Duc A. Nguyen; Steven Brakman; Harry Garretsen; Tristan Kohl (CESifo GmbH, 2024)
We study the post-war effects of the bombing of German cities during WWII on urban growth and use the synthetic control method (SCM) to construct comparison units for affected West-German cities. The reason to use SCM is that cities might experience structural changes that have nothing to do with the bombing of cities. Ignoring these structural changes could incorrectly attribute the decline of cities to the WWII bombing shock, while other factors are at work. The SCM takes these structural changes onboard. The synthetic units are used as counterfactuals to assess the long-run impact following the WWII bombing on the size distribution of 53 West-German cities. Our main contribution is that we do not only study whether bombed cities are mean-reverting, but also use the counterfactual to determine whether individual cities experienced a positive or negative impact. In general, we find mean reversion for 50-70% of cities, as well as a roughly balanced ratio of positively to negatively impacted cities.
Keywords: R12; C93; B40; 330; urban growth; synthetic control method; WWII shock; city size distribution